Implementasi Olahraga Memanah Dalam Pembentukan Karakter Religius Anak Berbasis Pendidikan Islam (Studi Kasus Anak Usia 6-12 Tahun di Master Archery Club Pangkalpinang) - Aziz, Devia (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Character education is an effort to inculcate intelligence in thinking, appreciation in the form of attitudes, and practice in the form of behavior that is in accordance with the noble values ​​that become his identity, manifested in interactions with God, oneself, among others, and the environment. Archery is a fun sport because the movements performed are not too varied, so it is not easy to shape and teach anyone. Archery is able to be one way to support children's character education because in archery there is a synergy between mind, physical, and mental into a unity that must be owned by an archer. For this reason, this research is research on the formation of religious character in children based on Islamic education in archery, a case study of children aged 6-12 years at the Master Archery Club in Pangkalpinang.